1981
DOI: 10.1016/0032-0633(81)90008-8
|View full text |Cite
|
Sign up to set email alerts
|

Non-thermal produced by dissociative recombination of O2+: A theoretical model and observational results

Abstract: Thermal and non-thermal O('D) number density profiles are calculated. The two populations are assumed to be coupled by a thermalization cross-section which determines the loss and production in the non-thermal and thermal populations, respectively. The sources, sinks and transport of the two populations are used to model volume emission rate profiles at 63OOA. The 6300 A brightness measured by the Visible Airglow Experiment is then used to establish the presence of the non-thermal population and to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…Such quiet time nonthermal oxygen atoms are thought to be produced mainly by dissociative recombination of O2+ and NO + [ Hickey et al , ], as opposed to charge exchange with precipitating O + during active times, as discussed in the present paper. Observational evidence of this nonthermal population utilizes various techniques: twilight observations of the 732.0 and 733.0 nm airglow emission from the ground [ Yee et al , ], redline intensity measurements made by the Visible Airglow Experiment on the Atmosphere Explorer‐C satellite [ Schmitt et al , ], red line temperature measurements from the FPI on the Dynamics Explorer satellite [ Hubert et al , ], and in situ measurements made by the low energy neutral atom (LENA) instrument on the IMAGE spacecraft [ Wilson and Moore , ]. This evidence is supported by modeling which suggests that a nonthermal population is present above 200 km, which should increase FPI red line temperature measurements above the ambient temperature [ Shematovich et al , ; Sipler and Biondi , ; Kharchenko et al , ].…”
Section: Discussionmentioning
confidence: 99%
“…Such quiet time nonthermal oxygen atoms are thought to be produced mainly by dissociative recombination of O2+ and NO + [ Hickey et al , ], as opposed to charge exchange with precipitating O + during active times, as discussed in the present paper. Observational evidence of this nonthermal population utilizes various techniques: twilight observations of the 732.0 and 733.0 nm airglow emission from the ground [ Yee et al , ], redline intensity measurements made by the Visible Airglow Experiment on the Atmosphere Explorer‐C satellite [ Schmitt et al , ], red line temperature measurements from the FPI on the Dynamics Explorer satellite [ Hubert et al , ], and in situ measurements made by the low energy neutral atom (LENA) instrument on the IMAGE spacecraft [ Wilson and Moore , ]. This evidence is supported by modeling which suggests that a nonthermal population is present above 200 km, which should increase FPI red line temperature measurements above the ambient temperature [ Shematovich et al , ; Sipler and Biondi , ; Kharchenko et al , ].…”
Section: Discussionmentioning
confidence: 99%
“…Using a simple model, Schmitt et al (1981) have interpreted an excess of the 6300Å intensity above 600 km as evidence of nonthermal O( 1 D) atoms. In 1999, Shematovich et al have reported their studies of thermalization with a Monte Carlo model and predicted an excess O( 1 D) temperature of 350 K at noon for low solar activity conditions at the altitude of 300 km.…”
Section: Discussionmentioning
confidence: 99%
“…These results, however, are weighted by the volume emission profile of the source emission along the line of sight, which is usually not known. The lifetime of the oxygen atom is sufficiently long for thermalization [Schmitt et al, 1981[Schmitt et al, , 1982, and the observed Doppler shift is taken to be representative of the general atmospheric motion.…”
Section: Measurements Of the Meridional Wind With The Fabry-perot Intmentioning
confidence: 99%